Sufficient space for the use of wind energy on land. A proposal for a new regulatory framework - von Seht, Hauke (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
In the course of the upcoming further restructuring of the energy system in Germany, it will be necessary to gradually provide additional areas for the use of wind energy on land. However, the current regulatory framework shows deficits which make the corresponding planning considerably more difficult and delay. Therefore, legislative changes are proposed in this paper to solve the problem. The resulting new dynamic control approach relies on gradual, optimized expansion values in the Renewable Energy Sources Act, on which the basic requirements in the Spatial Planning Act are based. The latter contain minimum requirements for regional planning priority areas – based on regular analyses to be introduced by the Bundesamt für Bauwesen und Raumordnung. If these values are adhered to, an encouraged partial deprivation of privilege in the building code would take effect, bymeans of which complex and error-prone concentration zone planning can be dispensed with in corresponding regions. At the same time, a change is proposed to accelerate the process, on the basis of which a permit for wind turbines in priority areas can be carried out in a legally secure manner, even in the case of opposing, as yet unadjusted municipal concentration zone plans.